ByzRev 03.2021.015: Sergei Mariev (ed.), Bessarion’s Treasure. Editing, Translating and Interpreting Bessarion’s Literary Heritage: (Byzantinisches Archiv – Series Philosophica 3). Berlin -- Boston: De Gruyter 2021. - Maruggi, Aurelia (The Byzantine Review, 2021)
Sergei Mariev (ed.), Bessarion’s Treasure. Editing, Translating and Interpreting Bessarion’s Literary Heritage (Byzantinisches Archiv – Series Philosophica 3). Berlin – Boston: De Gruyter 2021. 286 pp. – ISBN: 978-3-11-060180-0 (€ 89.95).